Dancing sprites: Detailed analysis of two case studies. Issue 6 (16th March 2017) - Soula, Serge; Mlynarczyk, Janusz; Füllekrug, Martin; Pineda, Nicolau; Georgis, Jean‐François; van der Velde, Oscar; Montanyà, Joan; Fabró, Ferran
Abstract: On 29–30 October 2013, a low‐light video camera installed at Pic du Midi (2877 m), recorded transient luminous events above a very active storm over the Mediterranean Sea. The minimum cloud top temperature reached −73°C, while its cloud to ground (CG) flash rate exceeded 30 fl min −1 . Some sprite events have long duration and resemble to dancing sprites. We analyze in detail the temporal evolution and estimated location of two series of sprite sequences, as well as the cloud structure, the lightning activity, the electric field radiated in a broad range of low frequencies, and the current moment waveform of the lightning strokes. (i) In each series, successive sprite sequences reflect time and location of corresponding positive lightning strokes across the stratiform region. (ii) The longer time‐delayed (>20 ms) sprite elements correspond to the lower impulsive charge moment changes (iCMC) of the parent strokes (<200 C km), and they are shifted few tens of kilometers from their SP + CG stroke. However, both short and long time‐delayed sprite elements also occur after strokes that produce a large iCMC and that are followed by a continuing current. (iii) The long time‐delayed sprite elements during the continuing current correspond to surges in the current moment waveform. They occur sometimes at an altitude apparently lower than the previous short time‐delayed sprite elements, possibly because of changes in the local conductivity. (iv) The largest and brightest sprite elements produce significant current signatures, visible when their delay is not too short ( 3–5 ms). Key Points: Dancing sprites repeat the timing and location of successive parent strokes Time‐delayed sprites correspond to current surges during the continuing current following the lightning strokes Delayed sprites can occur after an initial sprite and at lower altitude